Time management, fundamental strength application and managerial performance of public secondary administrators in the division of city schools, Manila: an assessment - Fernandez, Lolita Punzalan (Manila : National University, 2007)
This study was limited to the time management, fundamental strength application and managerial performances of public secondary school managers in the Division of City Schools in Manila in the school year 2005-2006.
Title page -- Approval Sheet -- Acknowledgement -- Abstract -- Table of Contents -- Chapter 1: The Problem and its Setting -- Chapter 2. Review of Related Literature -- Chapter 3.Methods, Procedures and Sources of Data -- Chapter 4. presentation, Analysis and Interpretation of Data -- Chapter 5. Summary, Conclusion and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research design: Descriptive-Developmental Method.
Includes bibliographical references.